INVESTMENT PROJECT ANALYSIS OF DIGITAL PRINTING MACHINE ACQUISITION: CASE STUDY OF PT. YUDHIS PRINTING - Yudistira, Andriana
Indonesia's printing industry is expected to grow until 2024, with 35,000 graphic companies and a 40% increase in imports of printing machines in 2024. The digital printing sector remains strong and relevant as long as printing management adopts new technologies, streamlines consumer needs, and offers a variety of products and services. The digital printing sector remains relevant and strong. The objective of this study is to examine the financial viability of investing in solvent printing machine units that produce two products: product A (flexi), like banners, and product B (stickers). MSMEs commonly utilize these products for promotional activities, community events, and other advertising purposes. Investment analysis of additional printing units includes the amount of investment needed, profitability, and project risk to produce investment decision proposals. This study will use capital budgeting techniques with the parameters Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). The financial model is based on a variety of assumptions derived from diverse perspectives and approaches. Risk analysis is also conducted to find variables that can affect business profitability using sensitivity analysis and scenario analysis. This study produces a financially feasible project with a total investment of Rp 281 million. The project has the potential to generate an NPV of Rp 288.4 million and an IRR of 69.84%. The investment is returned in less than two years of business operations, with a profitability index of 2.45. The results of the price risk assessment of product A (Flexi) are the most sensitive variables to changes in NPV, and inflation is the variable that least affects changes in NPV, with a swing of 0.08% in changes in NPV. Companies can increase marketing for solvent machine products to increase sales of product A, one of which is supporting several community activities and organizations for customer engagement and providing free design services and unlimited revisions, which is an added value for customers to keep ordering and reduce costs for customers. Online advertising through Facebook ads or Instagram ads can be a platform. By using scenario analysis with a 20% swing on each variable in the best scenario (+ 20% swing), this business can generate an NPV of IDR 481,098,237.16, and the worstcase scenario (-20% swing) produces an NPV of IDR 28,122,303.77.